Meso-Cenozoic paleotopographies and paleolandscapes in the Deseado Massif - Betard, F.; Peulvast, J.P.; Rabassa, Jorge Oscar; Aguilera, Emilia Yolanda
The Deseado Massif is the southernmost part of a continent, outside of Antarctica, where Gondwana Landscapes may be observed and investigated. This chapter presents preliminary observations and field data about the Gondwana Landscapes of this cratonic area of Southern Argentina, one of the most remote, isolated, and less populated places on Earth. Under extreme cold–arid climate conditions, the region presents very scarce vegetation cover, which further enables the geomorphological observations. Remnants of planation surfaces of undisputable Late Mesozoic age, developed on Jurassic volcanic units and covered by Late Cretaceous and Paleogene sedimentary rocks, are exposed along tens of thousands square kilometers of this cratonic unit. In those remote times, the climate of this portion of Patagonia was very wet and warm, allowing the development of extensive chemical weathering. Fil: Betard, F. Université Paris Diderot - Paris 7; Francia Fil: Peulvast, J.P. Sorbonne University; Francia Fil: Rabassa, Jorge Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Aguilera, Emilia Yolanda. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina